Neil Simon's Seems like old times [videorecording (DVD)] - Hamlisch, Marvin (Columbia Tristar Home Video, 2002)
A comedy in which a writer (Chase) is forced to be involved in a bank robbery, is on the run and turns to his ex-wife (Hawn) for help.